Variação fenotípica e reconstrução de caracteres ancestrais no gênero Cereus Mill. (Cactaceae) - Yano, Isis Minhós (Universidade Federal de São Carlos, 2021)
The genus Cereus Mill. (Cactaceae) is widely distributed throughout South America and has 26 recognized species (in addition to six subspecies), subdivided into four subgenera: Cereus, Oblongicarpi, Ebneria and Mirabella. In phylogenetic terms, the genus has at least five main lineages (A-E). In this work we investigate the phenotypic variation in Cereus species. The hypotheses are: 1) the phenotypic transitions along the phylogeny may be linked to the genus diversification in dry environments in South America and 2) there is enough phenotypic variation to discriminate species of different clades and/or subgenera. To test these hypotheses, the variation for 54 phenotypic characters was screened from the literature for all Cereus species and two external groups. To test hypothesis 1, a ancestral state reconstruction was performed. For this reconstruction, the software MESQUITE v.3.61 was used under the algorithms of Maximum Parsimony and Maximum Likelihood (Mk1), for taxa with defined phylogenetic position (20 species). To test hypothesis 2, discriminant analysis were performed using RStudio, STATISTICA and PAST software. Among the 54 characteristics sampled, 11 showed a significant change of state in the phylogeny, namely: root type (clade D, 99.9%), flower areolas (clade D, 99.9%), flower bracts (clade D , 99.9%), branches (clades B, 58.2%; D, 98.2%; and the two subspecies of C. fernambucensis Lemaire/Ritter, 58.4% and 60.4%), rib margins (clades A2, 88.1%; B, 59%; and the two subspecies of C. jamacaru De Candolle/Ritter, 87.2%), wood (clade D, 47.9% each sp), position of the outer segments perianth (clade A + B, 88.9%), dispersers (two subspecies of C. jamacaru plus C. pierre-braunianus E. Esteves Pereira, 96.2%), dehiscence (clade D, 99.6%), perianth remains (branches comprising clades A + B + C + C. fricii Backeberg, 77.8%), and minimal number of radial spines (clade C, 84%; the two subspecies of C. jamacaru, 81.6 %). State changes for clade D seem to be related to mitigation of the effects of transpiration and solar irradiation, in addition, rib characteristics may be linked to the dry environment, and to acting in the thermal control promoted by their shading. Tuberous roots are possibly associated with water and starch storage and can even function as vegetative propagation organs in plants that occur in adverse environments. Multivariate analyzes revealed that the Mirabella subgenus was very different from the other three subgenres. The adaptationist explanation is viable, but not a conclusion of this work, considering other processes that could lead to the same present observations.
Phenotipic variation and ancestral character reconstruction of genus Cereus Mill (Cactaceae)
Keywords: Reconstrução de caracteres ancestrais; Análise discriminante; Ancestral state reconstruction; Discrminant analysis; CIENCIAS BIOLOGICAS::BOTANICA::FITOGEOGRAFIA